Continuum strength of isoscalar transiton of α + 40Ca in 44Ti. Issue 9 (1st September 2020) - Nakao, M.; Umehara, H.; Nakamoto, R.; Ebata, S.; Ito, M.
ABSTRACT: Continuum strength function for the isoscalar monopole (IS0) and dipole (IS1) transitions in the α + 40 Ca system is investigated on the basis of the orthogonality condition model (OCM) under the absorbing boundary condition (ABC). The nuclear potentials are constructed from the double folding procedure with the effective nucleon–nucleon interaction of the density-dependent Michigan three range Yukawa. The OCM + ABC calculation predicts that the enhancement of the IS0 and IS1 strengths for the α – 40 Ca relative excitation occurs at the lower excitation energy of E ≤ 12 MeV. The strength of these transitions exceeds the transition strength in the single-particle excitation, which is observed at much higher energy region. The application of the low-lying enhancement in the IS0 and IS1 strengths to the nuclear transmutation is also discussed.